The influence of chemical modification of wood on its nucleation ability in polypropylene composites - Borysiak, S.; Doczekalska, B. (Polimery, 2022)
The crystallization of isotactic polypropylene in contact with pine wood was studied by hot stage polarizing microscopy. The agents applied to chemical treatment of wood were maleic, propionic, phthalic, crotonic or succinic anhydrides. Mercerization and extraction processes were used as well. The aim of this study was to analyze the influence of chemical modification of pine wood on its nucleation activity in polypropylene crystallization process. The occurrence of the transcrystallization layer (TCL) was found to be strongly dependent on the type of chemical treatment of wood surface. Predominant nucleation ability was establish for unmodified pine wood. However, mercerization and extraction processes of wood slightly decreased its nucleation ability in polypropylene matrixes. Moreover, it was determined that wood modified by anhydrides can enhance the transcrystallization layer of PP in comparison with wood mercerized or extracted. Unexpectedly, wood modified with succinic anhydride did not induce transcrystallization.